The Association Between NLRP3 and The Development of Depression in Type 2 Diabetes Patients - AL-Khaqani, Zahraa Mohammed; Al-Turaihi, Thanaa Shams Al-Deen (Medical Science Journal for Advance Research, 2024)
Background: Type 2 diabetes is a chronic disease characterized by two characteristics: insulin resistance and destruction of pancreatic beta cells, leading to high blood sugar levels. This disease is associated with many complications that can be serious and life-threatening, such as depression. The presence of inflammatory components like inflammatory cytokines and immune protein complexes in high concentrations in the blood of type 2 diabetes patients has led to theories and studies that support the involvement of certain inflammatory pathways in the relationship between these two diseases. Method: This cross-sectional study included the selection of 128 individuals diagnosed with type 2 diabetes from the Diabetes and Endocrinology Center located in Najaf, Iraq from August 2023 to October 2023. The study included 43 men and 85 women. The ages of the participants ranged from 30 to 75 years. Patients were randomly selected during their visit to the center.Depression was diagnosed using the Hamilton scale, a blood serum sample was taken, and the NLRP3 level was measured using the ELISA device. Result: The results ultimately showed that inflammasome levels were higher in people with depression than in patients with type 2 diabetes than in patients with diabetes who did not have depression, and the difference was statistically significant p-value (0.020).